2022
DOI: 10.3389/fgene.2022.821275
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Featured Metabolism-Related Genes and Imbalanced Immune Cell Subsets in Sepsis

Abstract: Sepsis is a heterogeneous disease state triggered by an uncontrolled inflammatory host response with high mortality and morbidity in severely ill patients. Unfortunately, the treatment effectiveness varies among sepsis patients and the underlying mechanisms have yet to be elucidated. The present aim is to explore featured metabolism-related genes that may become the biomarkers in patients with sepsis. In this study, differentially expressed genes (DEGs) between sepsis and non-sepsis in whole blood samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…Currently, there are still no effective treatment therapies to lower sepsis mortality due to the complex pathophysiology ( 27 , 28 ). Although sepsis is fundamentally associated with inflammation, recent studies have reported that metabolism, especially lipid metabolism, plays a critical role in the pathogenesis and pathophysiology of sepsis ( 23 , 29 ). Serum levels of the prostaglandins PGE 2 and PGD 2 , two eicosanoid lipid mediators, are found to be elevated in patients with sepsis, accompanying with increased COX-2 activity ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there are still no effective treatment therapies to lower sepsis mortality due to the complex pathophysiology ( 27 , 28 ). Although sepsis is fundamentally associated with inflammation, recent studies have reported that metabolism, especially lipid metabolism, plays a critical role in the pathogenesis and pathophysiology of sepsis ( 23 , 29 ). Serum levels of the prostaglandins PGE 2 and PGD 2 , two eicosanoid lipid mediators, are found to be elevated in patients with sepsis, accompanying with increased COX-2 activity ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rats were randomly divided into three groups: the control group, the sepsis group, and the SB203580-treated sepsis group. To establish a sepsis model, cecal ligation and puncture (CLP) were performed as previously described ( 23 ). SB203580 (500 μg/kg) was administered via the tail vein 30 minutes prior to sepsis induction, while the sepsis group received an equal volume of ddH2O in the same manner.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Zhu et al ( 2022 ) used high‐resolution untargeted metabolomics analysis to study influenza A virus subtype H1N1 (H1N1) infected patients and found an association between abnormal arginine metabolism produced by the virus and the immunity of the respiratory mucosa. She et al ( 2022 ) used untargeted metabolomics analysis to discover metabolic hub genes that may be biomarkers for precise therapy in sepsis patients. In their research, Ding et al ( 2021b ) used untargeted metabolomics analysis to identify glycerophospholipid (GPL) metabolism and glutamine and glutamate metabolism as potential key targets in HIV infection.…”
Section: Targeted and Untargeted Metabolomics For Immunology Researchmentioning
confidence: 99%
“…Mannose metabolism, amino sugar metabolism, starch metabolism, unsaturated fatty acid biosynthesis, platelet activation, and purine metabolism have some studies in sepsis ( Gao et al, 2015 ; Bakalov et al, 2016 ; Hwang et al, 2019 ; She et al, 2022 ). However, there are no relevant studies in Sepsis-induced myocardial dysfunction (SIMD).…”
Section: Introductionmentioning
confidence: 99%